2019
DOI: 10.1371/journal.pone.0217190
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of hippocampal NR2A/2B subunits related to cognitive impairment in a pristane-induced lupus BALB/c mice

Abstract: Neuropsychiatric systemic lupus erythematosus (NPSLE) is associated with learning and memory deficit. Murine model of lupus induced by pristane in BALB/c mice is an experimental model that resembles some clinical and immunological SLE pathogenesis. Nevertheless, there is no experimental evidence that relates this model to cognitive dysfunction associated with NR2A/2B relative expression. To evaluate cognitive impairment related to memory deficits in a murine model of lupus induced by pristane in BALB/c mice re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…For instance, iso urane up-regulated extrasynaptic NR2B in the hippocampus in elderly rats and impaired cognitive function [24]; and iso urane or sevo urane upregulated NR2B in the hippocampus, facilitated LTP in CA1 area, and improved cognition in adult mice [14,16]. Sevo urane induced NR1 and NR2B up-regulation, NR2A down-regulation in the PFC, and caused cognitive de cits in adolescent rats [71], while propofol down-regulated NR1, NR2B, NR2A, and PSD-95 in the PFC of developing rat brain, and caused long-term cognitive dysfunction [17,72]. The possible reasons for this discrepancy might be different ages, species of animals, and strategies of drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, iso urane up-regulated extrasynaptic NR2B in the hippocampus in elderly rats and impaired cognitive function [24]; and iso urane or sevo urane upregulated NR2B in the hippocampus, facilitated LTP in CA1 area, and improved cognition in adult mice [14,16]. Sevo urane induced NR1 and NR2B up-regulation, NR2A down-regulation in the PFC, and caused cognitive de cits in adolescent rats [71], while propofol down-regulated NR1, NR2B, NR2A, and PSD-95 in the PFC of developing rat brain, and caused long-term cognitive dysfunction [17,72]. The possible reasons for this discrepancy might be different ages, species of animals, and strategies of drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal injection of pristane to Balb/c mice develops an SLE-like disease with ANA and immune complex-mediated glomerulonephritis with high levels of IFN. It also results in downregulation of the GluN2A subunit of the NMDA receptor in hippocampal neurons and to disrupted learning and memory deficits 19 . Abnormal levels of IFN-α have been observed in the sera and cerebrospinal fluid (CSF) of patients with mental disorders 20,21 .…”
Section: Induced Mouse Modelsmentioning
confidence: 99%
“…Induction of memory long term potentiation (LTP) in the hippocampus requires agonistic activity on NMDA-R, while antagonists impair learning and memory capabilities 10 . Recently, it has been demonstrated that the downregulation of NMDA-R subunits is related to learning and memory disturbance in an animal model of neuropsychiatric systemic lupus erythematosus 11 . On the contrary, extracellular glutamate accumulation leads to an over-stimulation of glutamate receptors, including NMDA, hesitating in neurotoxicity 12 .…”
Section: Introductionmentioning
confidence: 99%